Augmented Reality Book Development for Elementary Visual Arts Education Using Smartphone-Based Photogrammetry - Nabil Oktanuryansyah, Muhammad; Kusumaningtyas, Ester Anggun; Hefira, Vania (ULTIMART Jurnal Komunikasi Visual, 2025)
This study develops an Augmented Reality (AR) book to support elementary visual arts learning by enabling intuitive interaction with three-dimensional (3D) forms, scale, and perspective. Using smartphone-based photogrammetry, the book integrates realistic 3D assets for visual exploration beyond two-dimensional (2D) illustrations. The prototype was evaluated through the AREA (Augmented Reality for Enterprise Alliance) heuristic framework to assess usability and functional design. Results show that most interface elements align with heuristic principles, though improvements are needed in navigation, layout, and asset optimization. Overall, the study highlights a set of heuristic insights and preliminary design principles for developing AR-based books: emphasizing multimodal cues, clear spatial orientation, and intuitive object manipulation as key factors to support students’ comprehension of artistic 3D objects. The results show that most interface features met heuristic principles, with Evaluator I recording 51.60% “Yes” responses, Evaluator II 35.20%, and Evaluator III 37.97%. The “No” category reached 45.38% for Evaluator II, while “Somewhat” remained low overall, with the highest from Evaluator III (8.10%). Future studies should expand user testing with elementary learners to validate these heuristic guidelines and refine the interactive design framework for broader educational application   Keywords: Augmented Reality, Heuristic Evaluation, Visual Arts Education, Photogrammetry